Symptoms related to mental disorder in healthcare workers during the COVID-19 pandemic in Brazil - Campos, Juliana Alvares Duarte Bonini [UNESP]; Martins, Bianca Gonzalez [UNESP]; Campos, Lucas Arrais [UNESP]; de Fátima Valadão-Dias, Filomena; Marôco, João (Springer Nature, 2021)
Background: Studies of previous pandemics indicate that healthcare workers have a high risk of developing symptoms related to mental health, especially depression, anxiety, and stress. Objective: To identify mental disorder symptoms among Brazilian healthcare workers during the Sars-Cov-2 pandemic and compare findings in different work categories. Methods: This was an online cross-sectional study. Information related to the pandemic and mental disorder symptoms was collected. The Depression, Anxiety, and Stress Scale and the Impact of Event Scale-revised were used. Associations were estimated by the chi-square test. The mean scores were compared among work categories with ANOVA (α = 5%) and the prevalence of symptoms was estimated. Results: 1,609 healthcare workers participated in the survey [mean age: 36.9 (SD = 11.6) years, women = 83.6%]. There was no association between work category and changes in mental health during the pandemic (p = 0.288) or prevalence of unsafe feeling (p = 0.218). A significant relationship was observed between maintaining work activities during the pandemic and work category (p < 0.001). Physicians had the lowest out-of-work prevalence (9.5%) while dentists had the highest (32.3%). Physicians and nurses showed the highest prevalence of in-person work routine. Psychologists presented the highest prevalence of remote work (64.0%) while dentists had the lowest (20.2%). A high prevalence of depression (D), anxiety (A), and stress (S) symptoms was observed in all professional categories (D: 57.2, 95% CI 48.3–66.1%; A: 46.20%, 95% CI = 37.2–55.2%; S: 55.80%, 95% CI = 46.8–64.8%), with physicians (D = 38.4%, A = 25.80%, S = 37.90%), psychologists (D = 50.2%, A = 39.0%, S = 43.1%), and nurses (D = 50.0%, A = 40.9%, S = 49.0%) having significantly lower scores. Psychologists had the lowest pandemic-related psychological impact (42.70%, 95% CI 36.8–48.6%). Conclusion: Extreme changes in the work routine of dentists and psychologists and an overall high prevalence of mental symptoms due to the pandemic were found. Researchers should focus on gathering information that can identify workers at increased risk of mental illness to guide discussions and develop actions to minimize the harm of the pandemic. In addition, we suggest that healthcare and support systems urgently adopt mental health care measures with specialized professionals to protect the psychological well-being of the healthcare community.
Keywords: Anxiety; COVID-19; Depression; Healthcare professionals; Pandemic; Stress